2014
DOI: 10.4149/bll_2014_091
|View full text |Cite
|
Sign up to set email alerts
|

Is physical activity a protective factor against pancreatic cancer?

Abstract: Abstract:Objectives: The objective of the study was to analyze an association between selected factors and pancreatic cancer, assuming that knowing the etiology would help infl uence the incidence of this severe type of cancer through primary prevention. In addition to age, gender, BMI and education, the analysis aimed at assessing occupational and leisure-time physical activities with respect to pancreatic cancer. Background: In numerous studies, physical activity is reported to be a protective factor against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
(19 reference statements)
1
12
0
1
Order By: Relevance
“…That is why risk factors for PDA are an important issue. It appears, from descriptive and retrospective studies, that tobacco smoking and aging are seriously involved in the development of pancreatic cancer [1, 2, 6, 7, 14, 18, 19]. It was reported that smoking is responsible for nearly 25% of PDA, and that carbon monoxide, benzene, vinyl chloride, and many other compounds play a destructive role not only in the development, but also in the progression of PDA.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…That is why risk factors for PDA are an important issue. It appears, from descriptive and retrospective studies, that tobacco smoking and aging are seriously involved in the development of pancreatic cancer [1, 2, 6, 7, 14, 18, 19]. It was reported that smoking is responsible for nearly 25% of PDA, and that carbon monoxide, benzene, vinyl chloride, and many other compounds play a destructive role not only in the development, but also in the progression of PDA.…”
Section: Risk Factorsmentioning
confidence: 99%
“…That is why our weight is one of the most important factors of our health. If we are becoming overweight earlier in life, we have a greater risk of consuming carcinogenic substances, energy imbalance, and inflammation [1, 3, 4, 6, 8, 15, 18]. …”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other evidence suggest that mTOR may also play a positive role in cancer patients. It has been demonstrated that physical exercise stimulates the mTOR pathway and this is correlated with the prevention of certain type of cancers [34][35][36]. mTOR can also increase tolerability of chemotherapy and can protect against autophagy (frequently associate with cancer resistance to therapy) and improve prognosis [37][38][39].…”
Section: Amino Acids Supplementation As a Cancer Fighting Weaponmentioning
confidence: 99%